Intrauterine Transmission of Hepatitis B Cannot Be Ruled Out by A Single Negative Hepatitis B e Antigen (HBeAg) Result among Hepatitis B Surface Antigen (HBsAg) - Positive Pregnant Women - Chalid, Maisuri Tadjuddin; Judistiani, Tina Dewi; Syahril, Rizalinda; Masadah, Rina; Febriani, Dwi Bahagia; Wahyuni, Ridha; Turyadi, Turyadi; Massi, Muh Nasrum (The Indonesian Biomedical Journal, 2024)
BACKGROUND: The risk factors for intrauterine transmission of hepatitis B virus (HBV) in hepatitis B surface antigen (HBsAg)-positive pregnant women are poorly understood. Numerous factors are considered to be involved, including placental barrier, obstetric environment, high viral load, and positivity of hepatitis B e antigen (HBeAg). This study was conducted to investigate the role of placenta barrier, clinical, and viral factors in intrauterine transmission of HBV.METHODS: A cross-sectional study was conducted involving 1,353 pregnant women who underwent HBsAg screening. Eighty-four (6.2%) women were detected as HBsAg positive and were examined for HBsAg level, anti-HBs, anti-HBc, HBeAg/hepatitis B e antibody (anti-HBe) status, and HBV DNA presence in cord blood. Quantitative HBV DNA was analyzed using real-time polymerase chain reaction (PCR).RESULTS: Eighty-four of 1,353 subjects were HBsAg-positive. HBV DNA was positive in 28/84 (33.7%) maternal sera, 19/79 (24.05%) placental specimens, and 9/83 (10.84%) in cord blood. There were significant associations between HBV DNA in maternal serum (p=0.000) and placental tissue (p=0.000) with HBV DNA in the cord blood. No clinical factors were associated with HBV DNA transmission in cord blood. Sixty percent of viral load >5.3 log10 copies/mL were found in the cord blood, of which 43.8% HBeAg positive and 3.1% HBeAg negative.CONCLUSION: Reduced transmission via compartments established the placenta’s barrier function in mother-to-child transmission. A high maternal viral load and positive HBeAg were risk factors for intrauterine transmission, while negative HBeAg still has the possibility of transmission.KEYWORDS: mother-to-child transmission, hepatitis B virus, intrauterine